A national survey: Evaluating current practice and risk assessment in morcellation amongst gynaecologists in the United Kingdom. (January 2020) - Ghai, Vishalli; Jan, Haider
Abstract: Objective: To evaluate current practice and adherence to AAGL and BSGE power morcellation guidelines. Study design: Cross-sectional survey. Setting: United Kingdom. Patients/Population: 157 National Health Service (NHS) hospital trusts (organisation comprising of one or more hospitals) offering gynaecological services. Intervention: A questionnaire was emailed between March–July 2018 and completed by Lead/ Directors of Gynaecology within each organisation. Descriptive statistics were used to present results from this study. Measurements/Results: We assessed power morcellation practice patterns, informed consent processes and outcomes over the last 12 months. We received 136 responses (87 % response rate). Power morcellation was performed by a third (59, 37.6 %) of all UK hospitals. The median number of gynecologists performing morcellation per organisation was 2 (Q1-Q3: 2–4). A median of 7 morcellators (Q1-Q3: 0–17) were purchased and 7 morcellators (Q1-Q3: 1.25–15.75) used per annum. A median of 10 (Q1-Q3: 2.0–15.0) laparoscopic hysterectomies and 5 (Q1-Q3: 0.5–9.0) myomectomies requiring morcellation were performed per annum. Almost, a third of hospitals did not perform an endometrial biopsy or MRI. 79.7 % (47) of trusts consented for power morcellation and 76 %, (46) explained risk of inadvertent leiomyosarcoma. 83.3 %, (50) had no patient literature and almost half had no audit process 45 %, (27). Conclusion: Current UK practice does not reflect recommendations from the AAGL or BSGE. Deficiencies were identified in pre-operative evaluation, local governance procedures, and consenting practices regarding use of a power morcellator and risk of occult leiomyosarcoma.